PERSON-BUSINESS FIT ANALYSIS: A STUDY OF SBM-ITB ENTREPRENEURSHIP STUDENTS BATCH 2018 - Rasnadipoetra, Kidam Aulia; Ginting, Henndy (Journal of Business and Management, 2018)
Abstract.The low level value of congruence between personality and the characteristics of a career field is one of the main reasons why many researchers studied about the personality congruence topic. Entrepreneurship, as one of the career field choices becomes the main discussion in this study. There have been many studies that explained about the congruence between personality and career field to find out how matched the personality with its work environment, and how the result affects their interest about their career field choice. The main goal of this study program is to create a generation of young and innovative entrepreneurs. However, almost half of the Entrepreneurship SBM-ITB students did not want to continue their own business after graduate from this school. The author tried to explore whether the personality of each students are congruence with their business field that had been chosen before based on HollandÃ¢â‚¬â„¢s theory. The subjects of this research were 60 students who were studied in Entrepreneurship study program. The instrument used in this research was the HollandÃ¢â‚¬â„¢s Self-Directed Search (SDS). The author also used the clusters from business field categories that have been converted into the Holland codes. The results of this research showed that the value of congruence between personality and business field that had been chosen by the students have a relatively low score. The results also showed that there is significant difference in personality between students who want to continue and those who do not want to continue their business. The result of the mean score of congruence within the students is 20.77 percent.Keyword: Person-Environment Fit, Congruence, Business Field, Entrepreneurship, Self-Directed SearchÃ‚Â